Anesthetic Cardioprotection in Relation to Mitochondria: Basic Science - Mio, Yasushi; Uezono, Shoichi; Kitahata, Hiroshi (Current Pharmaceutical Design, 2014)
Anesthetic pre- and postconditioning pharmacologically reduces ischemia/reperfusion injury. Mitochondria play a central role in these myocardial protective salvage effects. In the preconditioning, low levels of reactive oxygen species, which are produced by anesthetics in the mitochondria, act as a trigger to prevent cardiomyocytes death and modify intracellular signaling mechanisms. In the postconditioning, decreased mitochondrial matrix pH, which was caused by anesthetics, triggers the onset of a rapid protective effect. The mitochondrial membranes have several ion channels that act as major determining factors of cellular life and death under pathophysiological conditions. In these channels, the mitochondrial adenosine triphosphate-sensitive K+ channels, the mitochondrial Ca2+-activated K+ channels and mitochondrial permeability transition pores play critical roles in cardioprotection against ischemia/reperfusion injury. Mitochondrial permeability transition pores are end effectors, which contribute to myocardial preconditioning and postconditioning. Activation of intracellular signaling and acidification of mitochondrial matrix pH prevent the mitochondrial permeability transition pore opening, and therefore, preserve the mitochondrial function to supply adenosine triphosphate, resulting in myocardial protection due to the maintenance of intracellular homeostasis.
Keywords: mitochondria